2019
DOI: 10.2131/jts.44.121
|View full text |Cite
|
Sign up to set email alerts
|

Benzo[a]pyrene induces pyroptotic and autophagic death through inhibiting PI3K/Akt signaling pathway in HL-7702 human normal liver cells

Abstract: -Benzo(α)pyrene (BaP) possesses a forceful hepatotoxicity, and is ubiquitous in foods and ambient air. Our previous study found that BaP induced pyroptotic and autophagic death in HL-7702 human liver cells; the relevant mechanisms, however, remain unknown. This work was therefore to unravel the effects of the PI3K/Akt signaling pathway on pyroptotic and autophagic death triggered by BaP. Cells were treated with or without LY294002 (PI3K/Akt inhibitor) and IGF-1 (PI3K/Akt activator) before BaP exposure, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…It has been reported that Gossypol, Arsenic, and Cadmium induced the pyroptotic damage [13][14][15]. Our preliminary study also demonstrates that BaP caused hepatocytes damage via inducing pyroptosis [25,28]. Iso is a natural flavonoid with a luteolin structure that is widespread in some foods and edible plants [29,30].…”
Section: Discussionmentioning
confidence: 57%
“…It has been reported that Gossypol, Arsenic, and Cadmium induced the pyroptotic damage [13][14][15]. Our preliminary study also demonstrates that BaP caused hepatocytes damage via inducing pyroptosis [25,28]. Iso is a natural flavonoid with a luteolin structure that is widespread in some foods and edible plants [29,30].…”
Section: Discussionmentioning
confidence: 57%
“…Based on these findings, we hypothesized that selenium could protect cells from apoptosis by regulating the PI3K/AKT pathway. To examine this, we incubated MC3T3-E1 cells with 20 mM of LY294002 (the inhibitor of PI3K/AKT) (Li et al, 2019). We found that selenium rescued the cells from LPS-induced apoptosis.…”
Section: Selenium Protected Cells Through Pi3k/akt/mir-155 Signaling Pathwaymentioning
confidence: 99%
“…Indeed, additional experiments demonstrated a dose-dependent induction of SLC13A5 by BaP through concentrations up to 100 µM. Higher concentrations of BaP at and above 20 µM have previously been indicated to be toxic to hepatocytes [68,69]. Whether BaP causes cellular toxic responses and also contributes to its upregulation of SLC13A5 remains elusive.…”
Section: Ahr In the Slc13a5 Transcriptionmentioning
confidence: 99%